2014
DOI: 10.1007/s10803-014-2103-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Teaching Interaction Procedure to Social Stories: A Replication Study

Abstract: This study compared the teaching interaction procedure to social stories implemented in a group setting to teach social skills to three children diagnosed with autism spectrum disorder. The researchers taught each participant one social skill with the teaching interaction procedure, one social skill with the social story procedure, and one social skill was assigned to a no intervention condition. The teaching interaction procedure consisted of didactic questions, teacher demonstration, and role-play; the socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 24 publications
1
22
1
Order By: Relevance
“…The effectiveness of each of the three prompting strategies evaluated in the present study has been documented in prior studies using SSEDs (e.g., Au et al, 2015;Doyle et al, 1990;Jerome et al, 2007;Kassardjian et al, 2014;J. A.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The effectiveness of each of the three prompting strategies evaluated in the present study has been documented in prior studies using SSEDs (e.g., Au et al, 2015;Doyle et al, 1990;Jerome et al, 2007;Kassardjian et al, 2014;J. A.…”
Section: Discussionmentioning
confidence: 85%
“…It should be noted that MTL and CTD prompting systems have a rather robust literature base when compared to FPF. However, the literature evaluating the use of FPF has increased in recent years (e.g., Au et al, 2015;Kassardjian et al, 2014;J. A.…”
mentioning
confidence: 99%
“…Social stories can be used to emphasize a specific skill that a child needs to improve [Benish & Bramlett, ]. In the past decades, social story intervention had been applied to promote peer interactions (inviting friends, explaining an event to peers, sharing toys, playing turn‐taking), diminish stereotypical behaviors, reduce interruptive behaviors, and establish self‐regulation behaviors among preschool children [Agosta et al, ; Benish & Bramlett, ; Chan & O'Reilly, ; Crozier & Tincani, ; Hsu, Hammond, & Ingalls, ; Kassardjian et al, ; Kuoch & Mirenda, ; Litras, Moore, & Anderson, ; C. M. More et al, ; Thompson & Johnston, ; Vandermeer, Beamish, Milford, & Lang, ]. Increment of the expected behaviors and/or reduction in the unfavorable behaviors were observed in most of the above studies, indicating that social story intervention could serve as a potential approach for behavior management among young children.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study, Leaf et al (2010) demonstrated the effectiveness of the TIP in teaching social skills within a group instructional format for individuals, ages ranging from 4 years old to 6 years old, diagnosed with ASD. Leaf et al (2012) and Kassardjian et al (2014) in studies comparing the relative effectiveness of the TIP to Social Stories™ both showed the TIP to be more effective and more facilitative of generalization when used to teach individuals with ASD social skills. Kassardjian et al (2013) showed the successful generalization of social skills taught using the TIP to the natural environment with four individuals with ASD, ages ranging 4-13 years old.…”
Section: Optional External Consequencementioning
confidence: 97%